1996
DOI: 10.1046/j.1526-4610.1996.3605316.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Migraine in Medical Students

Abstract: The purpose of this study was to investigate the prevalence of migraine in medical students, as well as its clinical aspects and impact. All 595 medical students of Santa Casa School of Medicine of São Paulo, Brazil were asked if they had experienced any kind of headache in the past year. Those who responded positively were further investigated by an appropriate questionnaire. Diagnosis of migraine was based on the International Headache Society criteria of 1988. Forty percent of students suffered from some ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
56
6
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 6 publications
16
56
6
11
Order By: Relevance
“…Our findings of higher pre valence of headaches among women is consistent with several other studies 5,[6][7][8][9][10]21,22 . In our study, the overall lifetime headache prevalence among men (97%) and women (100%) and the last-year prevalence among men (86%) and women (93%) were comparable with previous reports by Deleu et al 9 and Costa et al 6 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings of higher pre valence of headaches among women is consistent with several other studies 5,[6][7][8][9][10]21,22 . In our study, the overall lifetime headache prevalence among men (97%) and women (100%) and the last-year prevalence among men (86%) and women (93%) were comparable with previous reports by Deleu et al 9 and Costa et al 6 .…”
Section: Discussionsupporting
confidence: 93%
“…Studying headaches among university students is important, based on the premise that this population may be more subject to headaches than the general population, for reasons relating to academic life that are known to trigger headaches 5,10,12 , such as emotional stress and poor sleeping and feeding habits (including abusive use of caffeine and other psychoactive substances). Medical students and psychology students are similarly exposed to risk factors that trigger headaches and, in our study, we recruited students from the Schools of Medicine and Psychology for convenience sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, 552 (79.7%) of the study subjects belonged to 18-25 years of age constituting the majority. Our study showed high prevalence of migraine in females 461(62.1%) compared to that of males 236(33.8%), as already demonstrated in previous studies conducted by Bindu Menon et al [17] , Galinovic et al [18] and Sanvico et al [19] . However this finding should be interpreted with caution as our sample had more female participants.…”
Section: Discussionsupporting
confidence: 88%
“…Rassmussen, na Dinamarca, encontrou prevalência ao longo da vida entre 93 e 96% 2 . Pesquisas realizadas no Brasil chegaram a resultados semelhantes 14 . No entanto, considera-se classicamente a prevalência da cefaléia do tipo tensional como sendo maior que a da migrânea.…”
Section: Discussionunclassified